Strengthening Tax Audit Management by Controlling and Auditors' Competence: Tax Court Case in Indonesia - Wardayani , Wardayani; Santoso, Muhammad Rifky (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The Directorate General of Taxes (DGT) has proper tax audit management regulations, but the implementation still needs to be improved so that audits become effective. To find out these needs, a case study is conducted by discussing the dispute in the Tax Court Decision. This article finds that there is still a lack of communication between units in the DGT in the audit process, the use of professional judgment by the auditor is not fully following the regulations but it is effective, the follow-up audits are still incomplete, and the honesty in conveying facts is a problem. Disputes can be resolved when the required data from the other tax offices are available at the Court. If this data is available at the time of the audit, then there is no need for a dispute. This article suggests the need to increase controlling and competence of tax auditors. Controlling needs to improve during the audit process as well as evaluation of the results of follow-up audits, especially when it involves other units in the DGT such as the tax offices. The competence is enhanced by understanding the industry of the audited taxpayer.